Challenges Encountered and Opportunities of BSHM Graduates of BCP in Internship Program Amidst the Pandemic A.Y. 2021-2022: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Covid-19 pandemic outbreak forced many schools and colleges to remain closedtemporarily. Various schools, colleges, and universities have discontinued in-person teachingand implemented virtual classes. Graduate students experience taking virtual internshipprograms and encounter challenges such as internet connection, device availability, workingstudents and working environment, and limited opportunities in hospitality management andentrepreneurship.According to the data, the bulk of the respondents are between the ages of 21 and 25. Most ofthem are male and 24 years old in terms of the respondent's employment status amidst thepandemic. Of the respondents, 100 percent, 26 respondents are employed. The majority ofthe respondents strongly agree with the challenges they encountered in terms of internetconnection, device availability, working students and working environment, and limitedopportunities in hospitality management and entrepreneurship during their virtual internshipprogram.Based on the gathered data and conclusions drawn, researchers formulated solutions thatcan be recommended on the challenges encountered and opportunities of BSHM graduatesof BCP in internship programs amidst the pandemic.
Keywords: Hospitality Management